Molecular and immunomodulatory actions of new antiasthmatic agents: exploring the diversity of biologics in Th2 endotype asthma - Okwuofu, Emmanuel Oshiogwe; Chee, Audrey Hui Yong; Chee, Jonathan Woei Lim; Stanslas, Johnson (Academic Press, 2022)
Asthma is a major respiratory disorder characterised by chronic inflammation and airway remodelling. It affects about 1–8% of the global population and is responsible for over 461,000 deaths annually. Until recently, the pharmacotherapy of severe asthma involved high doses of inhaled corticosteroids in combination with β-agonist for prolonged action, including theophylline, leukotriene antagonist or anticholinergic yielding limited benefit. Although the use of newer agents to target Th2 asthma endotypes has improved therapeutic outcomes in severe asthmatic conditions, there seems to be a paucity of understanding the diverse mechanisms through which these classes of drugs act. This article delineates the molecular and immunomodulatory mechanisms of action of new antiasthmatic agents currently being trialled in preclinical and clinical studies to remit asthmatic conditions. The ultimate goal in developing antiasthmatic agents is based on two types of approaches: either anti-inflammatory or bronchodilators. Biologic and most small molecules have been shown to modulate specific asthma endotypes, targeting thymic stromal lymphopoietin, tryptase, spleen tyrosine kinase (Syk), Janus kinase, PD-L1/PD-L2, GATA-3, and CD38 for the treatment and management of Th2 endotype asthma.